1996
DOI: 10.1021/ma960552v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Kinetics of Nitroxide-Controlled Free Radical Polymerization

Abstract: The bulk polymerization of styrene at 125 °C in the presence of a PS−TEMPO adduct was studied with respect to the polymerization rate and the concentration of free TEMPO as a function of time, where PS is polystyrene and TEMPO is 2,2,6,6-tetramethylpiperidinyl-1-oxy. The results were perfectly consistent with the proposed kinetic scheme which assumes the existence of a stationary state with respect to both polymeric and nitroxyl radical concentrations and predicts that the polymerization rate of the nitroxide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
353
1
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 337 publications
(382 citation statements)
references
References 31 publications
25
353
1
3
Order By: Relevance
“…Because [P ⅐ ] Ӷ [X ⅐ ] in general, the difference in the quasi-equilibrium from (exact) equilibrium is important. To solve eqs 3 and 4, we here consider the limiting case with R i ӷ 0, first treated by Fukuda et al, 15 and the other limiting case with R i ϭ 0, first treated by Fischer 14 by a different approach than the one 9 given later. For more general cases, see refs.…”
Section: Rate Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because [P ⅐ ] Ӷ [X ⅐ ] in general, the difference in the quasi-equilibrium from (exact) equilibrium is important. To solve eqs 3 and 4, we here consider the limiting case with R i ӷ 0, first treated by Fukuda et al, 15 and the other limiting case with R i ϭ 0, first treated by Fischer 14 by a different approach than the one 9 given later. For more general cases, see refs.…”
Section: Rate Lawsmentioning
confidence: 99%
“…15 ). According to eq 2, the concentration of terminated PS radicals, [P] t , is roughly given by [P] …”
mentioning
confidence: 99%
“…After purification [11], Br-PS-Br was isolated with M n = 3000 and M w /M n = 1.07 according to PS-calibrated GPC. The initiation efficiency of DBMPM was confirmed to be virtually 100% by 1 H NMR (Fig.…”
Section: Preparation Of 14-di-(2-bromopropionyloxymethyl)benzene (Dbmentioning
confidence: 99%
“…After purification [11], PS-Br was isolated with M n = 1500 and M w /M n = 1.09. A chain extension test [14] showed that this polymer contains 4% of potentially inactive species (without bromide at the chain end: f dead = 0.04).…”
Section: Preparation Of ω-Bromopolystyrene (Ps-br)mentioning
confidence: 99%
“…(2001), Matyjaszewski and Davis (2002)). Nitroxide mediated CRP has been studied extensively by many researchers such as Georges et al (1996), Fukuda et al (1996), Georges et al (1997), Georges et al (1998), Wannemacher et al (2003), Braun (2005, and others.…”
Section: Introductionmentioning
confidence: 99%